Plant population is the function of grain yield of maize - MAK Mian; SS Kakon; ST Zannat3; AA Begum (Open Journal of Plant Science - Peertechz Publications, 2021)
A field experiment on hybrid maize with different plant population density was conducted at the Agronomy field of BARI, Joydebpur, Gazipur during the consecutive rabi season of 2019-2020 and 2020-2021. Five plant population density viz; T1= 66666 plants/ha (75cm × 20cm spacing: 6.67 plants/m2), T2= 83333 plants/ha (60cm × 20cm spacing:8.33 plants/m2), T3=100000 plants/ha (50cm × 20cm spacing:10 plants/m2), T4=125000 plants/ha (40cm × 20cm spacing:12.5 plants/m2) and T5=166666 plants/ha (30cm × 20cm spacing:16.67 plants/m2) were used in the experiment. LAI (leaf area index) and TDM (total dry matter) increased with the increase of plant population, those influenced grain yield of maize. The highest grain yield (10.12-10.78 t/ha) was recorded in T3 (100000 plants/ha) and the lowest (5.02-5.33t/ha) in T5 (166666 plants/ha) treatment. Functional relationship between plant population and grain yield of maize was established as Y = 2.0795x-0.1067x2; (R² = 0.92). The effect of plant population on the grain yield of maize could be explained 92% by the functional model. The co- efficient indicated that increase of one plant/m2 would increase grain yield at the rate of 2.0795 t/ha up to a certain limit. The estimated optimum plant population was 9.74 plants/m2 (974000 plants/ha) through functional model. Then the predicted maximum grain yield would be 10.13 t/ha at that optimum plant population of 9.74 plants/m2 (974000 plants/ha). There existed a good consistency between observed and predicted grain yield of maize (r=0.96 at p<0.01 and R2=0.97; using the developed functional model).